Coastal Polynya Disrupts the Acoustic Backscatter Diurnal Signal Over the Eastern Laptev Sea Shelf - Dmitrenko, Igor A.; Petrusevich, Vladislav Y.; Kosobokova, Ksenia; Komarov, Alexander S.; Bouchard, Caroline; Geoffroy, Maxime; Koldunov, Nikolay V.; Babb, David G.; Kirillov, Sergei A.; Barber, David G. (Frontiers in Marine Science, 2021)
The diel vertical migration (DVM) of zooplankton is one of the largest species migrations to occur globally and is a key driver of regional ecosystems and the marine carbon pump. The dramatic changes in the Arctic environment in recent years, mainly associated with sea-ice decline, may have wide significance for the Arctic shelf ecosystems including DVM. Observations have revealed the occurrence of DVM in ice-covered Arctic waters, however, there have yet to be observations of DVM from the extensive Siberian shelves in the Eurasian Arctic and no analysis of how the sea-ice decline may affect DVM. Here, 2 yearlong time series of acoustic backscatter, collected by moored acoustic Doppler current profilers in the eastern Laptev Sea from August 1998 to August 1999, were used to examine the annual cycle of acoustic scattering, and therefore the annual cycle of DVM in the area. The acoustic time series were used along with atmospheric and oceanic reanalysis and satellite data. Our observations show that DVM did not occur during polar night and polar day, but is active during the spring and fall transition periods when there is a diurnal cycle in light conditions. DVM began beneath the fast ice at the end of polar night and increased in intensity through spring. However, the formation of a large polynya along the landfast ice edge in late March 1999 caused DVM to abruptly cease near the fast ice edge, while DVM persisted through spring to the start of polar day at the onshore mooring. We associate this cessation of synchronized DVM ∼1 month ahead of polar day with a predator-avoidance behavior of zooplankton in response to higher polar cod abundance near the polynya. During polar day, the intensity of acoustic scattering was attributed to the riverine suspended particles. Overall, our results highlight the occurrence of DVM on the Siberian shelves, the cessation of synchronized DVM when a polynya opens up nearby, and the potential impact of significant trends toward a more extensive Laptev Sea polynya as part of changing ice conditions in the Eurasian Arctic and their impact on the Arctic shelf ecology.